2016
DOI: 10.1242/dev.141762
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Crumbs prevents ectopic Notch activation in developing wings by inhibiting ligand-independent endocytosis

Abstract: Many signalling components are apically restricted in epithelial cells, and receptor localisation and abundance is key for morphogenesis and tissue homeostasis. Hence, controlling apicobasal epithelial polarity is crucial for proper signalling. Notch is a ubiquitously expressed, apically localised receptor, which performs a plethora of functions; therefore, its activity has to be tightly regulated. Here, we show that Drosophila Crumbs, an evolutionarily conserved polarity determinant, prevents Notch endocytosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 86 publications
1
22
1
Order By: Relevance
“…Pharmacological interventions, such as γ-secreting enzyme inhibitor, Notch-1 ligand, and Akt and Hif-1α inhibitors were used to clarify the specific molecular mechanism. Notch signaling affected the morphogenesis of normal cells, 25 including the differentiation of multipotent progenitor cells, apoptosis, cell proliferation, cell boundary formation, 26 and the occurrence, progression, and metastasis of tumors. 27 Sahlgren reported that hypoxia resulted in elevated expression of Notch downstream genes and HIF-1α, which was stabilized in hypoxia and was found to interact with NICD and enhance its stability.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological interventions, such as γ-secreting enzyme inhibitor, Notch-1 ligand, and Akt and Hif-1α inhibitors were used to clarify the specific molecular mechanism. Notch signaling affected the morphogenesis of normal cells, 25 including the differentiation of multipotent progenitor cells, apoptosis, cell proliferation, cell boundary formation, 26 and the occurrence, progression, and metastasis of tumors. 27 Sahlgren reported that hypoxia resulted in elevated expression of Notch downstream genes and HIF-1α, which was stabilized in hypoxia and was found to interact with NICD and enhance its stability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results suggest that the trafficking of Crb and Serp may influence each other, adding an extra layer of coordination to the system. Actually, a role for Crb in regulating endocytic trafficking has been already proposed [64]. Indeed, several reports indicate that polarity proteins are both cargoes and regulators of endocytic recycling [65].…”
Section: Discussionmentioning
confidence: 99%
“…This releases Notch intracellular domain (ICD) to translocate to the nucleus where it forms a complex with the transcription factor CBF-1/Suppressor of Hairless/Lag1 (CSL), along with additional cofactors that activate gene transcription ( Figure 2). Additional routes to activation have also been described in both invertebrate and vertebrate models, which are independent of ligand binding [12][13][14][15][16][17][18]. These ligand-independent mechanisms, best characterised in Drosophila, depend on endocytosis of full-length Notch and proteolytic activation in the endosomal and lysosomal membranes ( Figure 2) [13,14,19,20].…”
Section: Introductionmentioning
confidence: 98%